BENIGN PHYLLODES TUMOUR WITH CYSTIC SQUAMOUS METAPLASIA: A RARE HISTOLOGY FINDING - Zafar, Shaista; Elsheikh, Tagwa; Baig, Mirza Sharjil; Iqbal, Javeria (Journal of Ayub Medical College Abbottabad, 2023)
Phyllodes tumour (PT) comprises 0.3-1% of all breast cancers and 3% of fibroepithelial neoplasm. It occurs more commonly in the fourth and fifth decades of life. Fibroepithelial neoplasms are composed of cells types with two different origins, commonly mesenchymal and epithelial. Histological features are important as this forms the basis of the categorization of PT into benign, borderline and malignant types, thus facilitating management. Metaplasia in any of the two components of PT is rare and the cystic squamous type of metaplasia has even more infrequent histological features. Case: This paper presents the case of a 63-year-old female with a palpable lump in the lower outer quadrant of left breast. Histology showed a benign Phyllodes tumour with patchy, cystic squamous metaplasia within the lesion, keratin production and foreign-body reaction in response to keratin spillage. The previously done core biopsy was also reviewed, which showed focal stromal cell condensation and features overlapping between benign and borderline phyllodes tumours. Conclusion: The case was presented because of its unique and rare histological picture of Cystic squamous metaplasia in benign PT and a further rarer finding of foreign body reaction to keratin spillage.